(untitled) (Modern education and development, 2025)
This article explores the impact of modern technologies on the development of independent thinking skills among primary school students. It discusses how digital tools, interactive learning platforms, and educational applications contribute to creating a learner-centered environment that encourages curiosity, critical inquiry, and self-guided learning. The study emphasizes the importance of integrating technology thoughtfully to foster analytical thinking, decision-making, and problem-solving abilities from an early age. It also highlights the role of teachers in guiding students to use technology responsibly and productively. The paper provides examples of effective practices and outlines recommendations for optimizing the use of modern technology in primary education.